Development of a software program for module allocation and interconnection optimisation in high-level synthesis of VLSI systems - Goo, Chong Kiat. (2008)
The objective of this project is to search for a new algorithm to solve the module allocation and interconnection problems. Current algorithms and techniques were studied and a new technique was developed and implemented.